A note on the weak law of large numbers for weighted negatively superadditive dependent random variables. Issue 21 (2nd November 2022) - Naderi, Habib; Boukhari, Fakhreddine; Matuła, Przemysław
Abstract: In this paper, we extend Kolmogorov–Feller weak law of large numbers for weighted random variables. In particular some results known so far for i.i.d. sequences are obtained for negatively superadditive random variables which are stochastically dominated.